Development and Preclinical Evaluation of Preparation Effectiveness for the Treatment of Hard Tooth Tissues after Temporary Filling Removal - Kopytov, Alexander A. (Asian Journal of Pharmaceutics (AJP), 2019)
Objective: The purpose of this study was development and preclinical study of the effectiveness of antiseptic liquid for the purification of dentinal tubules. Liquid application is planned after extraction from the prepared carious cavity of a temporary filling. According to the recommendations of clinicians, liquid should be sufficiently flowable to penetrate the lumen of the dentinal tubules and wash out fragments of temporary filling materials. At the same time, having an antiseptic effect, it should not change the strength characteristics of tooth hard tissues. Materials and Methods: Teeth, removed by orthodontic indications, were sealed with Clip Tripack materials (VOCO, Germany) and Restavrin Tempo (Tehnodent, Russia). Sealed teeth were kept in distilled water. Temporary fillings made of Clip Tripack materials and Restavrin Tempo were removed with an excavator from the teeth. Teeth were divided into two groups. The cavities of the first group of teeth were washed with one of the 12 variants of the test fluid, they were longitudinally sawn, and the surface of the cavity was examined with a scanning electron microscope. The cavities of the second group of teeth were washed with one of the 12 variants of the ultrasound-controlled test fluid, sawed, and microscopized. Visualization assessed the purity of the dentinal canal lumens. In addition, the antiseptic potential of 12 variants of the test liquid was evaluated. Results: Five variants of the ratio of components of antiseptic liquid for cleaning dentinal tubules from the remnants of the temporary filling material correspond to the task in hand. Conclusion: Antiseptic liquid for cleaning the dentinal tubules, made according to the compositions, in the described variants No. 1, 4, 5, 7, and 10, allows to effectively remove the remnants of the temporary filling material from the lumens of the dentinal tubules. Ultrasound activation reduces the evaporation time of the antiseptic liquid, which reduces the time of the cleaning procedure, and as a consequence, the patient’s stay in the chair, while not reducing its effectiveness.